Time-resolved imaging of correlation-driven charge migration in light-induced molecular magnets by X-ray scattering. (10th February 2021) - Tremblay, Jean Christophe; Pohl, Vincent; Hermann, Gunter; Dixit, Gopal
Abstract : Time-resolved current densities and X-ray scattering simulations yield information about the charge migration mechanism in laser-driven molecular magnets. Abstract : In this contribution, we investigate the effect of correlation-induced charge migration on the stability of light-induced ring currents, with potential application as molecular magnets. Laser-driven electron dynamics is simulated using density-matrix based time-dependent configuration interaction. The time-dependent many-electron wave packet is used to reconstruct the transient electronic current flux density after excitation of different target states. These reveal ultrafast correlation-driven fluctuations of the charge migration over the molecular scaffold, sometimes leading to large variations of the induced magnetic field. The effect of electron correlation and non-local pure dephasing on the charge migration pattern is further investigated by means of time-resolved X-ray scattering, providing a connection between theoretical predictions of the charge migration mechanism and experimental observables.